Effect of processing conditions of hot pressurized solvent extraction in batch reactor on anthocyanins of purple field corn - Rattana Muangrat (2018)
© 2018, Int. Comm. of Agricultural and Biosystems Engineering. All rights reserved. Total anthocyanin content of the dried kernel and dried cob of purple field corn was investigated under hot pressurized solvent extraction conditions. The highest total anthocyanin content of 492.51 µg cyanidin-3-glucoside g-1 dry weight of sample was obtained from dried kernel extraction using water-ethanol ratio 1:3 as solvent at sample-solvent ratio 1:8 and extraction temperature of 80οC. For the dried cob extraction, the highest total anthocyanin content obtained was 1890.49 µg cyanidin-3-glucoside g-1 dry weight of sample using water-ethanol ratio 1:1 as solvent at sample-solvent ratio 1:8, and extraction temperature of 100οC. The extraction was carried out at pressure of 0.20 MPa and 15 min with N2 purging. Additionally, the antioxidant activities assessed by DPPH, ABTS and FRAP assays showed that the dried cob extract exhibited the greatest antioxidant activity in DPPH assay (IC50=3.83 mg mL-1), ABTS assay (IC50=3.84 mg mL-1) and FRAP assay (421.76 mmol FeSO4 100 g-1 dry weight of sample).